The fate and behavior of petroleum biomarkers in diluted bitumen and conventional crude oil exposed to natural sunlight in simulated seawater. (April 2023) - Yang, Zeyu; Shah, Keval; Courtemanche, Claire; Hollebone, Bruce P.; Yang, Chun; and,; Beaulac, Vanessa
Abstract: Given that the physicochemical properties of diluted bitumen (dilbit) can differ from those of conventional crude oil, understanding the fate and behavior of this petroleum product in the environment becomes vital. This study involves the analysis of the photolytic behavior of some representative petroleum biomarkers, bicyclic sesquiterpanes (BSs), admantanes (ADs), diamantanes (DAs), and mono- and triaromatic steranes (MASs and TASs), by exposing Cold Lake Blend (CLB) and Alberta Sweet Mixed Blend (MSW) to winter and summer insolation after being spilled onto artificial brines. Aromatic steranes in all control samples remained relatively stable, whereas the biomarkers of BSs, ADs, and DAs were less stable. Similar to the exhaustive loss of the C 10 – C 17 alkanes, 91%–99% of BSs, ADs, and DAs were lost after five days of insolation, especially in summer. Both MASs and TASs were lost gradually in most scenarios, although both of them were lost faster in MSW than observed for CLB. The removal of MASs and TASs did not differ significantly from each other, although their loss was less than observed for PAHs having similar number of rings and greater than for the C 21 – C 33 n -alkanes. Therefore, photooxidation, not evaporation or biodegradation, was the main factor responsible for oxidizing these aromatic steranes. However, biomarkers of BSs, ADs and DAs were mostly lost through evaporation. Therefore, aromatic steranes have the potential to be utilized to evaluate the photolytic behavior of petroleum hydrocarbons, while BSs, ADs, and DAs should not be used for this purpose. Graphical abstract: Image 1 Highlights: BSs, ADs, DAs, MASs and TASs were analysed in solar irradiated CLB and MSW. BSs, ADs, and DAs were exhaustively evaporated like the C10–C17 range alkanes. The photolysis of MASs and TASs were slower than PAHs at the similar aromatic rings. The photolytic loss of MASs and TASs were greater than alkanes at same carbon range. Only MASs and TASs can be used to evaluate photolytic behavior of petroleum oil.